Konstruksi Sosial Nicky Astria Sebagai Lady Rocker Indonesia - Yully Hidayah; Een Herdiani; Retno Dwimarwati (Pascasarjana ISBI Bandung, 2022)
The focus of this study is on the social construction of Nicky Astria as a singer on the influence of the development of rock music in Indonesia. The term “constructive” refers to the structuralist-constructive theory of Pierre Bourdieu or better known as social constructivism or postmodernism which recognizes the role of subjects and objects in the development of science. The theory is then applied to map, analyze, and e xplain the construction including the realm, habitus, and capital which represent Nicky Astria as a Lady Rocker. The research method applied is Kuntowijoyo approach, namely history to understand life records, namely the era that is the background of the biography and the socio-political environment. Qualitative data are obtained by literature study, observation of the works and figures of Nicky Astria and interview with Nicky Astria and other sources related to Nicky Astria as the research subject. The results of the study shows that Nicky Astria as Lady Rocker is represented through her consistency and popularity in the world of rock music. Her activities and productivities color and contribute to the development of rock music in Indonesia.Keywords: Nicky Astria, structural constructive, Lady Rocker